Answer:
![(dy)/(dx)=(((2x-2)(x^3+3)-(x^2-2x)(3x^2))/((x^3+3)^2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/o2u5rctltt92uw31iuh7lt83ea70i3vvzx.png)
Explanation:
So we want to find the derivative of the rational equation:
![y=(x^2-2x)/(x^3+3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sd55c5o5mzje2xqrzmzypihn0gfj2e09be.png)
First, recall the quotient rule:
![((f)/(g))'=(f'g-fg')/(g^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5u1ztngnpgk0ev59fd519mz6ksd5qzokva.png)
Let f be x^2-2x and let g be x^3+3.
Calculate the derivatives of each:
![f=x^2-2x\\f'=2x-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/xg8y5nz20s3t8c6sf0o5gsin31stqr5ng7.png)
![g=x^3+3\\g=3x^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/fuype9h7ft3w7etdibsv0t5xy6rfok76pc.png)
So:
![(dy)/(dx)=((x^2-2x)/(x^3+3))'](https://img.qammunity.org/2021/formulas/mathematics/high-school/dncxcxax1dftvpzk626yait4mo65zownqc.png)
Use the above format:
![(dy)/(dx)=(f'g-fg')/(g^2)\\(dy)/(dx)=(((2x-2)(x^3+3)-(x^2-2x)(3x^2))/((x^3+3)^2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/n3qdmswxt4ay3epxxo407em45x3cj5ishh.png)
And that's our answer :)
(If you want to, you can also expand. However, no terms will be canceled.)